From Custom to Statute: A Historical and Legal Analysis of Land Tenure Systems in Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
Land tenure systems in Nigeria are deeply rooted in the nation’s historical evolution, from pre-colonial customary practices to colonial impositions and post-independence legal reforms. This paper examines the intersection of Nigerian history and property law, arguing that contemporary land disputes and inefficiencies in the legal framework are direct consequences of unresolved historical tensions. The study employs an interdisciplinary methodology, combining legal analysis of key statutes (notably the Land Use Act of 1978) with historical review of colonial archives, customary traditions, and post-independence land conflicts. The paper first explores pre-colonial landholding systems, emphasizing communal ownership and kinship-based rights. It then analyzes how British colonial policies (e.g., the Public Lands Acquisition Act of 1917) disrupted these systems, introducing individual ownership and state control. The post-colonial period, marked by the Land Use Act, further centralized land administration, often clashing with customary norms. Case studies, such as urban land disputes in Lagos and resource conflicts in the Niger Delta, illustrate the enduring legal-historical friction. Findings reveal that Nigeria’s property law remains a contested hybrid of imported statutes and resilient customary practices, with implications for economic development and social equity. The paper concludes with recommendations for legal reform, including decentralization of land governance and clearer integration of customary rights into statutory frameworks. By bridging historical scholarship and legal analysis, this research contributes to ongoing debates on land reform in post-colonial states.